EOR technologies for fractured-vuggy carbonate condensate gas reservoirs - Hedong Sun; Shiyin Li; Zhiliang Liu; Baohua Chang; Chunguang Shen; Wen Cao (Natural Gas Industry B, 2023)
There are abundant marine carbonate rock resources in China, which are dominated by fractured-vuggy carbonate oil and gas reservoirs accounting for over two thirds of proved reserves. The fractured-vuggy carbonate condensate gas reservoir in the Tarim Basin is at a burial depth of 4500–7000 m with the characteristics of extremely strong reservoir heterogeneity, complicated and diverse reservoir seepage media, complex fluid properties and quite difficult static characterization, which brings many challenges to reserve evaluation, development plan design and performance analysis. In order to improve the recovery factor of this type of oil and gas reservoir, this paper takes the dynamic characterization to supplement the static characterization and combines each other to improve the accuracy. In addition, based on many years' of dynamic and static research and development practice, the key enhanced gas recovery (EGR) technologies for fractured-vuggy carbonate condensate gas reservoirs are innovatively developed, such as the high-accuracy dynamic characterization technology with dynamic and static iteration for fractured-vuggy body in the strongly attenuated area of desert by taking seismic inversion information as the basis and 3D numerical well test as the core, the multi-target 3D development technology in one well to improve reserve production of fractured-vuggy condensate gas reservoirs, and the gas-lift depressurization EGR technology for fractured-vuggy condensate gas reservoirs. In conclusion, this technological system better solves the key difficulties in the fine characterization of fractured-vuggy body, reserve production improvement and abandonment pressure reduction of well. What's more, it realizes the fine reservoir characterization of fractured zones and feather-shaped fractured zones and the accurate prediction of key development indexes, and increases the deployment success rate of effective wells and efficient wells by 26% compared with that in the initial stage of large-scale productivity construction. To sum up, these technologies provide powerful technical support and reference experience for the scientific and efficient development of fractured-vuggy carbonate condensate gas reservoirs.